PENGARUH LATIHAN PUSH UP TERHADAP KETERAMPILAN TEKNIK DASAR SMASH BOLA VOLI ESKTRAKURIKULER SMP NEGERI 3 KARAWANG TIMUR - Muhammad Raihan Rahmanto; Setio Nugroho; Abdul salam Hidayat (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of Push Up training on Basic VolleyballSmash Extracurricular Skills at SMP NEGERI 3 KARAWANG TIMUR. This studyused an experimental method with a sample of 25 students, the mean Pretest scorewas an average score of 81.20 with a mean Posttest score of 77.20, experiencing asignificant increase of 1.86. After conducting a normality test, the results showedthat the pretest and posttest data were normally distributed with a value above0.05. The results of the study indicate the influence of the use of push up trainingon basic volleyball smash skills. therefore, in line with the title of the Influence ofPush Up training on Basic Extracurricular Volleyball Smash Skills, SMP NEGERI3 KARAWANG TIMUR states that the results of the study are that push up trainingis a basic extracurricular volleyball smash skill.